1983
DOI: 10.1093/ajcn/38.2.169
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative aspects of selenium utilization in pregnant and nonpregnant women: an application of stable isotope methodology

Abstract: Selenium utilization of women in early and late pregnancy was compared to that of nonpregnant controls. A defined diet providing about 150 micrograms Se/day was fed for 20 days, and selenium balance was measured during the last 12 days. Net selenium retentions of the women in early and late pregnancy were 10 and 23 micrograms/day, respectively, but probably are inflated estimates of the increased selenium requirement during pregnancy. Apparent absorption of selenium was 80% for all three groups. Pregnant women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…Similar observations were made in Finland by Antilla et al [ 14], in Germany by Behne and Wolters [ 15], and in the USA by Butler et al [16] and by Swanson et al [17], All these authors found that dcreases in Se concentrations were significant from the 1st to the 2nd and from the 2nd to the 3rd trimester of pregnancy. Quite recently, Lechner et al [18] observed that during the 3rd trimester of preg nancy, the plasma Se level was significantly lower than that of non-pregnant women.…”
Section: Discussionsupporting
confidence: 80%
“…Similar observations were made in Finland by Antilla et al [ 14], in Germany by Behne and Wolters [ 15], and in the USA by Butler et al [16] and by Swanson et al [17], All these authors found that dcreases in Se concentrations were significant from the 1st to the 2nd and from the 2nd to the 3rd trimester of pregnancy. Quite recently, Lechner et al [18] observed that during the 3rd trimester of preg nancy, the plasma Se level was significantly lower than that of non-pregnant women.…”
Section: Discussionsupporting
confidence: 80%
“…In populations with low selenium intake, urinary selenium correlates well with plasma selenium [23,30]. Several investigators reported that selenium status is apparently dropping with the progression of pregnancy, which was accompanied by the slow decrease in plasma selenium concentration, plasma glutathione peroxidase activity [31][32][33], and urinary selenium excretion [34], although a tendency toward renal selenium conservation revealed by Swanson et al [34] was questioned in a later study [25]. The changes of selenium status in pregnant women occurred independently of dietary selenium intake, inasmuch they were supplemented [22,25].…”
Section: Discussionmentioning
confidence: 99%
“…Although the Se requirement during pregnancy are unknown, on a defined diet of 150 lg of Se per day, pregnant women had an increased conservation of Se compared with nonpregnant women [22]. Because of the many variables associated with the Se intakes of people, quantitative estimates attempted for specific population groups have not been precise.…”
Section: Discussionmentioning
confidence: 99%